The Evaluation of Drug Delivery Nanocarrier Development and Pharmacological Briefing for Metabolic-Associated Fatty Liver Disease (MAFLD): An Update - Reem Abou Assi; Ibrahim M. Abdulbaqi; Chan Siok Yee (MDPI AG, 2021)
Current research indicates that the next silent epidemic will be linked to chronic liver diseases, specifically non-alcoholic fatty liver disease (NAFLD), which was renamed as metabolic-associated fatty liver disease (MAFLD) in 2020. Globally, MAFLD mortality is on the rise. The etiology of MAFLD is multifactorial and still incompletely understood, but includes the accumulation of intrahepatic lipids, alterations in energy metabolism, insulin resistance, and inflammatory processes. The available MAFLD treatment, therefore, relies on improving the patient's lifestyle and multidisciplinary pharmacotherapeutic options, whereas the option of surgery is useless without managing the comorbidities of the MAFLD. Nanotechnology is an emerging approach addressing MAFLD, where nanoformulations are suggested to improve the safety and physicochemical properties of conventional drugs/herbal medicines, physical, chemical, and physiological stability, and liver-targeting properties. A wide variety of liver nanosystems were constructed and delivered to the liver, only those that addressed the MAFLD were discussed in this review in terms of the nanocarrier classes, particle size, shape, zeta potential and offered dissolution rate(s), the suitable preparation method(s), excipients (with synergistic effects), and the suitable drug/compound for loading. The advantages and challenges of each nanocarrier and the focus on potential promising perspectives in the production of MAFLD nanomedicine were also highlighted.